Corporate Social Responsibility as a Reputation Mechanism for the Companies Operating in the Media Industry - Dejan Kružić; Miroslav Ivić; Lana Cindrić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
The purpose of this paper is to give an overview of the topic dealing with corporate social responsibility (CSR) effects on corporate reputation. By structuring past research, this paper aims to improve the understanding of how CSR is capable to enhance the corporate reputation of companies operating in the media industry. When it comes to CSR, media companies hold a specific position compared to companies across other industries. As business entities, media companies are expected to adopt CSR practices while at the same time being able to shape public opinion on the importance of CSR across other industries. This paper contributes to the existing literature by developing a framework that integrates existing research in this field.
Keywords: 650; corporate social responsibility; CSR; corporate reputation; media industry